Comparative studies of silver based catalysts supported on different supports for the oxidation of formaldehyde - Chen, D.; Qu, Z.; Shen, S.; Li, Xin Yong; Shi, Y.; Wang, Y.; Fu, Q.; Wu, J. (2011)
Temperature programmed desorption (TPD) and temperature programmed surface reaction (TPSR) were employed to study the HCHO adsorption–desorption and the surface reaction on Ag based catalysts supported on different supports (MCM-41, SBA-15, NaY, SiO2 and TiO2). According to the analysis of XRD, UV–Vis and H2-TPR for the as-prepared catalysts, there are four kinds of silver species on the supports, including metallic Ag particles (Ag0) with subsurface oxygen species, isolated Ag+ ions, well dispersed Ag2O and View the MathML sourceAgnδ+ clusters. Moreover, the states, the dispersion and the amount of these silver species seem to be obviously different on different supports. No activity for HCHO oxidation is observed on any supports, and silver particles with some oxygen in bulk were more active for the adsorption and activation of HCHO. MCM-41 and SiO2 supported silver catalysts give new adsorption sites for HCHO, and it is easily activated at lower temperatures and shows better surface reaction activity for HCHO oxidation. The desorption temperature for HCHO over SBA-15 and NaY supported silver catalysts is relatively higher, and its reaction performance is worse. However no surface reaction is observed on Ag/TiO2 catalyst during experiments. It is also found that HCHO molecular adsorbed on silver sites could be was oxidized into dioxymethylene (DOM) and formate surface species, and they reacts with oxygen to form CO2 during TPSR. The activities of different silver based catalysts for HCHO oxidation were closely related to their abilities for the formation of DOM and formate species.